A Comparison of Two Physical Activity Education Programs for Eighth-Grade Students: Effects on Awareness, Performance, and Self-Efficacy - Hossein Ashtarian; Parvin Bagheri; Farzad Jalilian; Afshin Almasi (Iranian Journal of Nursing and Midwifery Research)
Background: Physical activity is a key determinant of adolescent health. However, many female adolescents do not meet the recommended levels of activity. Although educational interventions have been implemented to address this issue, the role of maternal involvement in such programs has not been thoroughly examined. This study aims to bridge this gap by comparing the effects of two physical activity education programs on eighth-grade students’ awareness, performance, and self-efficacy. Materials and Methods: This semi-experimental study was conducted in 2020 on eighth-grade female students in Khomein, Iran. Six schools were randomly selected, and participants were randomly assigned to three groups: student, student-and-mother, and control. A total of 165 participants were included, with 55 individuals in each group. Data were collected using three questionnaires assessing physical activity awareness, self-efficacy, and performance. Data analysis was conducted using SPSS version 25. Statistics analysis, including one-way ANOVA, Kruskal-Wallis test, paired t-test, and Wilcoxon test were used to compare the groups. p < 0.05 was considered statistically significant. Results: There were no statistically significant differences in demographic characteristics among the three groups. The changes in knowledge scores within the student and student-and-mother groups were not statistically significant (p = 0.288); however, both groups demonstrated significantly higher scores compared to the control group (p < 0.001). Regarding performance scores, the student-and-mother group showed a statistically significant improvement over the student group (p < 0.039), and both groups outperformed the control group significantly (p < 0.001). The difference in self-efficacy score in the student-and-mother group was more than that in the student group and was statistically significant, and was higher in both groups than in the control group (p < 0.001). Conclusions: This study highlights the effectiveness of educational interventions in improving students’ awareness, performance, and self-efficacy, with maternal involvement serving as a key factor in enhancing these outcomes.